Three‐dimensional assessment of the pharyngeal airway in Japanese preschoolers with orofacial clefts. (12th April 2019) - Takahashi, Masahiro; Yamaguchi, Tetsutaro; Lee, Myoung K.; Suzuki, Yoko; Adel, Mohamed; Tomita, Daisuke; Nakawaki, Takatoshi; Yoshida, Hiroshi; Hikita, Yu; Furuhata, Mayu; Tsuneoka, Misato; Nagahama, Ryo; et al.
Abstract : Objectives/Hypothesis: Individuals with orofacial clefts often experience respiratory problems because of nasopharyngeal abnormalities. Pharyngeal airway morphology is thought to differ among the various cleft types. We measured three‐dimensional (3D) airway volume using cone‐beam computed tomography (CBCT) analysis to evaluate and compare pharyngeal airways in Japanese preschoolers with and without orofacial clefts. Study Design: Retrospective case‐control study. Methods: We enrolled 83 subjects (37 boys, 46 girls; mean age = 4.66 ± 0.56 years) with nonsyndromic orofacial clefts and 16 noncleft healthy subjects (seven boys, nine girls; mean age = 5.30 ± 0.52 years) as controls. The subjects were divided into five groups. Four groups were based on the cleft type: isolated cleft palate, unilateral cleft lip and alveolus), unilateral cleft lip and palate, and bilateral cleft lip and palate. The fifth group included the noncleft controls. All subjects were examined with CBCT, and the 3D airway volume was measured. We analyzed group differences statistically using analysis of covariance with the Bonferroni post hoc pairwise comparison tests for the corrected means. Results: Compared with the noncleft group, each cleft group exhibited significantly decreased total and nasal airway volumes and increased superior and inferior pharyngeal airway volumes. The differences were all statistically significant. Conclusions: Our findings suggest that anatomical differences exist in pharyngeal airway volumes among various cleft groups and in those without a cleft. Level of Evidence: 3b Laryngoscope, 130:533–540, 2020